Compliant curved-crease origami-inspired metamaterials with a programmable force-displacement response - Ting-Uei Lee; Yan Chen; Michael T. Heitzmann; Joseph M. Gattas (Materials & Design, 2021)
Origami-inspired metamaterials utilise geometric sheet transformations to generate and control novel material mechanical properties. The majority of research effort has been devoted to straight-crease origami-inspired metamaterials, however curved-crease origami, which allows compliant folding and bending behaviours, has significant potential for adoption. This study proposes a new type of compliant curved-crease origami-inspired metamaterial, constructed with an ‘elastica’ non-zero principal surface curvature. Construction parameters for the new metamaterial are shown to influence a range of non-linear force–displacement response characteristics, including response shape, response duration, and response magnitude. A concise analytical curved-crease bending translation (CCBT) method is developed for rapid response prediction from metamaterial geometric parameters. The CCBT method also then enables the direct design and specification of a metamaterial with a fully programmable compliant force–displacement response.